Analysis of the Mechanism for Implementing Corporate Social Responsibility (CSR) in Relation to Applicable Laws and Regulations in Batu Bara Regency - Joe, Alvin; Pinasang, Dani Robert; Soepeno, Muhammad Hero (Jurnal Indonesia Sosial Sains, 2026)
This study examines the implementation of Corporate Social Responsibility (CSR) in Batu Bara Regency, focusing on its alignment with applicable laws and regulations. The main objective is to identify gaps between legal expectations and actual practices in CSR implementation, particularly regarding program budgeting, beneficiary selection, proposal submission, and reporting obligations. A qualitative approach using a case study design was employed, involving companies in the region that are required to carry out CSR under national and local regulations. In-depth interviews were conducted with company representatives, local government officials, and community stakeholders. The findings reveal that CSR implementation in Batu Bara Regency often deviates from legal norms, with significant issues in transparency, accountability, and compliance. Companies frequently fail to report CSR budgets and activities as required by regulations, and the beneficiary selection process lacks consistency. Additionally, there is a lack of effective monitoring and weak enforcement of sanctions for noncompliance. The study recommends strengthening regulations, improving coordination between companies and local governments, simplifying submission processes, and increasing community participation to ensure that CSR programs meet legal standards and effectively promote community welfare.